Anxieties, age and motivation influence physical activity in patients with myeloproliferative neoplasms - a multicenter survey from the East German study group for hematology and oncology (OSHO #97) - Felser, Sabine; Rogahn, Julia; le Coutre, Philipp; Al-Ali, Haifa Kathrin; Schulze, Susann; Muegge, Lars-Olof; Gruen, Julia; Geissler, Jan; Kraze-Kliebhahn, Veronika; Junghanss, Christian (Frontiers in Oncology, 2023)
Background: Physical activity (PA) is a non-pharmacological approach to alleviate symptom burden and improve health-related quality of life (HrQoL) in cancer patients (pts). Whether pts with myeloproliferative neoplasms (MPN) PA behavior changes due to symptom burden and/or knowledge of the putative beneficial effects of PA has not yet been investigated. Methods: We performed a large questionnaire study in MPN pts. Self-reported PA behavior and potential influencing factors of 634 MPN pts were analyzed. Questionnaires were used to assess demographics, anxiety, severity of symptoms, HrQoL, current level of everyday and sports activities, and the level of information regarding the importance/possibilities of PA. According to their PA, the pts were assigned to the three groups: “inactive”, “non-targeted active”, and “sporty active” and compared with each other. Results: Key findings are that in 73% of the pts, the disease had an impact on PA, with 30% of pts reducing their PA. The prevalence of anxieties (e.g., occurrence of thrombosis and bleeding) regarding PA was 45%. Sporty active pts had a lower symptom burden and better HrQoL (p ≤ 0.001) compared to the other groups. Inactive pts were significantly older and had a higher body mass index than sporty active pts. Inactive and non-targeted active pts felt less informed about the importance/possibilities of PA (p = 0.002). Conclusion: Our results suggest that especially older and non-sporty MPN pts could benefit from motivational as well as disease-specific PA information. This study was registered at the German Registry of Clinical Trials, DRKS00023698.